(untitled) (International Journal of Innovative Research in Engineering & Management, 2021)
With a large number of cities and villages, India is the second highest populated country in the world. In India, villages still house a sizable percentage of the people. To better their socioeconomic situation, small cottage businesses that may employ local residents should be developed. The industries included in the programme are small cottage businesses that operate during the day and close at night. These businesses need a steady supply of electricity. However, due to its geographic constraints, the area has seen a significant loss of supply and has frequently finding electricity inadequate to run the equipment. As a result, industry expansion would be impeded, and local residents’ development would be affected. Renewable energy, on the other hand, may be produced and utilized on-site, enhancing supply reliability. They have a cheap operating cost because they are renewable in nature. However, because renewable energy output is entirely dependent on weather conditions, a battery bank must be used as a backup.. This backdrop describes a way for combining solar PV with wind energy. The system considers integrating solar PV and wind energy to satisfy demand because they compliment each other in nature. The software may be used independently. The system runs several permutations of the model to find the most optimum model capable of providing consistent, acceptable quality, and cost-competitive electricity. The strategy also researches and analyses the degree of renewable penetration to minimize carbon footprint, investigates combinations to reduce capital investment, and focuses on decreasing the levelized cost of energy.